Digital Leadership Competencies for Deck Officers: A Curriculum Development Framework for Indonesian Maritime Academies in Industry 4.0 Contexts (International Journal of Economics Management and Social Science, 2026)
The global maritime industry undergoes rapid technological transformation, yet maritime education curricula remain disconnected from industry 4.0 requirements. This qualitative study examines digital leadership competencies required by contemporary shipping operations and investigates how Indonesian maritime academies can systematically integrate these competencies into deck officer training programs. Through thematic analysis of interviews with 35 maritime experts (shipping company commanders, port authority managers, and maritime educators), this research identifies critical digital leadership competencies spanning technical literacy, meta-competencies for technological adaptation, and transformational competencies for organizational change leadership. Results reveal significant gaps between current maritime education offerings and industry expectations, particularly regarding decision-making under algorithmic uncertainty, cybersecurity awareness, and data-driven command authority. A proposed pedagogical framework integrates digital leadership competencies into existing curricula while maintaining maritime safety standards and classical seamanship foundations. Findings demonstrate that effective digital leadership development requires interdisciplinary curriculum redesign, faculty professional development initiatives, and industry-academic partnership models. This research provides evidence-based recommendations for maritime educators, institutional leadership, and industry stakeholders regarding optimal strategies for competency assessment, curriculum design, and continuous professional development pathways for maritime officers transitioning into digitally-intensive shipping environments. Keywords :  Maritime leadership; Digital transformation; Curriculum development; Competency framework; Maritime education; Industry 4.0; Deck officer training